Seasonal-Spatial of Putrajaya Lake Water Quality Parameter (WQP) Concentration Using Geographic Information System (GIS) - Asmat, Arnis; Atiqah Hazali, Nur; Nasuha Mat Nor, Anis; Khairunnisa Zuhan, Fatin (International Journal of Engineering and Technology, 2018)
This study presents the assessment of selected water quality parameters (WQP) distribution at Putrajaya Lake during the dry and wet season using spatial analysis. The WQP used in this study were dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammonia-nitrogen (NH3-N), total suspended solid (TSS), pH and temperature. Total thirteen water samples were obtained during both dry and wet seasons from May 2015 until March 2016 distributed throughout the areas. To explore the WQP distribution, Inverse Distance Weighted (IDW) was employed. The results have shown that mean values of WQ concentration during dry and wet season are varies accordingly. The highest value parameters of water quality during dry season which are COD (17.2 mg/L), DO (7.11 mg/L) and NH3N (0.94 mg/L). Meanwhile on the wet season, the highest values are recorded for BOD (5.27 mg/L), pH (7.62 mg/L) and TSS (18.4 mg/L) respectively. This has indicated that the concentration of WQP in the lake changed seasonally. Furthermore, among the WQPs; DO, TSS and COD have exhibited significant relationship between others for both seasons.Â Â